Low-density lipoprotein-cholesterol lowering effect of a nutraceutical regimen with or without ezetimibe in hypercholesterolaemic patients with statin intolerance - Ward, Natalie C.; Reid, Christopher M.; Watts, Gerald F. (Frontiers in Cardiovascular Medicine, 2022)
Background: Statins are the most widely prescribed medication to lower low-density lipoprotein cholesterol (LDL-c). However, a significant portion of patients are unable to tolerate them due to side effects, most commonly muscle related. Nutraceuticals, natural plant derivatives with lipid-lowering properties, may provide an alternative to lower LDL-c in these patients. Aims: To investigate whether a nutraceutical regimen, either alone or in combination with ezetimibe, can lower LDL-c in patients with hypercholesterolaemia who are intolerant to statins. Methods: Participants were recruited into a double-blind, randomised, placebo-controlled intervention study. Treatments were (i) placebo, (ii) nutraceutical (500mg berberine, 200mg red yeast rice, 2g plant sterols)/daily, (iii) ezetimibe (10mg)/daily, or (iv) the combination of nutraceutical and ezetimibe/daily. At baseline and week 8, all participants provide a fasting blood sample for assessment of lipid profile and safety bloods. Results: Fifty participants were randomized, with 44 completing the treatment period. Following adjustment for baseline levels and compared with placebo, LDL-c was significantly reduced (all p<0.0001) with ezetimibe (-1.02 mmol/L), nutraceutical (-1.15 mmol/L) and the nutraceutical and ezetimibe combination (-1.92 mmol/L). Non-HDL cholesterol was significantly reduced (all p<0.0001) with ezetimibe (-1.29 mmol/L), nutraceutical (-1.37 mmol/L) and the nutraceutical and ezetimibe combination (-2.18 mmol/L). Remnant cholesterol and triglycerides was significantly reduced with the nutraceutical and ezetimibe combination (p=0.018). Conclusions: A nutraceutical regimen (berberine, red yeast rice and plant sterols) and ezetimibe independently and additively lower LDL-c in patients with hypercholesterolaemia who are intolerant to statins.